THE IMPACT OF THE EDUCATIONAL SERVICES MARKET ON THE INNOVATIVE DEVELOPMENT OF THE NATIONAL ECONOMY (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the context of an increasingly competitive environment in the world, the importance of developing and improving the effectiveness of innovation systems in higher education is increasing as a leading factor in economic development. One of the main goals for improving the competitiveness of a national economy is to choose priority strategic directions. This article examines the impact of educational services on innovative development in a country's economy. It also looks at how principles of national innovation can be applied to economic policy, and how countries' competitiveness can be measured.
Keywords: educational services, higher education institutions, innovative development, competitiveness, national economy, efficiency.